The Best Learning Methods to Improve Student's Discus Throw Abilities in SMP Negeri 24 Makassar - Hanafi, Suriah; Hakim, Hikmad; Sahabuddin, Sahabuddin (UNIVERSITAS NEGERI MAKASSAR, 2023)
This study aimed to determine the difference between learning methods (A) which consist of the overall method (A1), the partial method (A2), and the combination method (A3), in increasing students' discus throw abilities (Y). This study used a 3 x 2 factorial experimental method, with the study's target population being 134 male students of SMP Negeri 24 Makassar. The sampling used was a purposive sampling technique by selecting 27% of the highest score data, and 27% of the lowest score referred to the Verducci theory. Hypothesis test results: (1) the overall method value was higher than the partial method value (A1 x A2) with a p-value of 0.002 (h1 accepted); (2) The overall method value was higher than the combination method value (A1 x A3) with a p-value of 0.02 (H1 accepted); and (3) The partial method value was higher than the combination method value (A2 x A3), with p-value 0.006 (h1 accepted). Thus it could be concluded that the overall learning method was better than the partial or combination method.